THE EFFECT OF VARIATION IN PREHEATING TEMPERATURE AND HADRFACING TREATMENT ON THE PHISYCAL AND MECHANICAL PROIPERTIES OF MEDIUM CARBON STEEL - Basuki, Rio; Waluyo, Joko; Huda, Saiful; Lestari, Nidia (TRAKSI, 2024)
Welding is joining two or more metal parts by heating the metal until it melts and then adding material (electrode) to fuse like a complete object. The welding process on steel causes the metal around the weld area to experience changes in the thermal cycle, so before welding, providing preheating treatment with temperatures of 100°C, 150°C, and 200°C, then on the surface of the metal and to increase its hardness, a further process is carried out namely the hard facing process.   Hardfacing is a process where a harder material is applied to a parent material through welding. The hard-facing method is carried out by melting the HV-600 electrode wire on a plate until it obtains the desired thickness, resulting in a harder microstructural change on the metal surface. This research aims to determine the effect of preheating temperatures of 100°C, 150°C, and 200°C on the physical and mechanical properties of AISI 1040 steel material which is heat faced with HV – 600 electrodes in the Shield Metal Arch Welding process. The tests carried out in the research for physical properties were microstructure, and for mechanical properties were hardness and wear. The results of microstructure research at preheating temperatures of 100°C, 150°C, and 200°C, the magnitudes are 79.52%, 72.01%, and 68.56% respectively and the hardness values are 79.6 HRC, and 78 HRC respectively. and 75 HRC while the wear values are 0.0000587 m3/kg.m, 0.0000873 m3/kg.m and 0.0000917 m3/kg.m. From the results of this research, the optimum hardness and wear values are hard-facing with the preheating temperature of 100°C.